Penerapan Model Problem Based Learning Berbantuan Puzzle Pecahan Untuk Meningkatkan Hasil Belajar Matematika Siswa Sekolah Dasar - Kholifah, Umi Nur; Mukti, Lola Indra; Ermawati, Diana (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2024)
This research was motivated by the use of learning models that students did not like, low understanding of fraction material, and low learning outcomes in mathematics learning. This research aims to improve mathematics learning outcomes with a problem based learning model assisted by fraction puzzles at SD Negeri Purworejo 01. This research method is classroom action research. The subjects of this research were class III, totaling 21 students, consisting of 11 male students and 10 female students. The research procedure consists of planning, implementation, observation and reflection with data collection techniques using observation, interviews and tests, while data analysis techniques use quantitative and qualitative data analysis. The research results showed that there was an increase in student learning outcomes in each cycle, from cycle I an average of 70, equivalent to 33% in the good category, and in cycle II it increased with an average of 83.57, equivalent to 71% in the very good category. The conclusion of this research is that the Problem Based Learning Model assisted by fraction puzzles can improve the mathematics learning outcomes of class III students at SD Negeri Purworejo 01.